Effect of light emission on polymerization of luting resins - Ghavam M.; Ataei M.; Baik F. (Tehran University of Medical Sciences, 1999)
Indirect esthetic restorations have recently gained popularity, and choosing suitable cement is"nan important concern in this regard. A wide variety of resin cements with different curing models:"n(chemical, light, dual), have been introduced to the profession, and among them the dual systems are"nclaimed to be able to continue polymerization after stopping the light. In order to study and compare the"npolymerization process of different curing systems, this research was performed."nThe present study measured the degree of conversion (DC) of three types of resin cements: a self cured,"na light cured and a dual cured cement. The samples were prepared as follows:"n1-The self cured samples were made according to the manufacturer."n2-The light cured samples were exposed to the curing light for 60 seconds, through a 2 mm thick wafer"nof porcelain."n3- The dual cured samples were divided into 2 groups. The first was lighted similar to the light cured"nsamples, and the second did not receive any light."nThe degree of polymerization was measured by FTIR at time levels of 5, 10,20,30,45,60 minutes and 24"nhours post mixing. The infrared spectrum of the samples were recorded and degree of conversion were"ndetermined. The results demonstrated an increase in mean DC of all groups at post mixing time, but this"nwas significant only in the lighted dual cured cement (PO.05). The light cure resin showed high DC at"nthe base line time (5min). At the end of 60 minutes, the self cure resin had the most DC. The unlighted"ndual cement had a very low DC and didn't improve in polymerization during the post mixing controls."nThe lighted dual cement had a significant improve in curing at post mixing times, and it was"nsignificantly different from unlighted dual cement. So the dual cure cement needs to receive sufficient"nlight energy to initiate the curing process and the chemical component of this cement could not improve"nthe DC completely."nAfter 24 hours migration of unpolymerized monomers, seams to decrease the DC at the surfaces and"nremoving the most superficial layer, showed that the underlying parts, had improved DC. It seems that in"norder to be sure of what happens at the restoration-tooth interface, it is appropriate to use self cure"ncements with improved flow and film thickness.